1970
DOI: 10.3126/on.v8i1.4325
|View full text |Cite
|
Sign up to set email alerts
|

Site-wise Mercury Levels in Ulhas River Estuary and Thane Creek near Mumbai, India and its Relation to Water Parameters

Abstract: Ulhas river estuary (73°14′E, 19°14′N to 72°54′E, 19°17′N) and Thane creek (72°55′E, 19°N to 73°E, 19°15′N) near Mumbai, India are highly polluted owing to the heavy load of industrial pollutants and sewage discharge. The traditional fisher-folk living along the banks of Ulhas river estuary and Thane Creek rely on these contaminated fish for their daily sustenance, thereby being exposed to heavy mercury pollution for several years. However, little attention has been given to the levels of mercury in water, its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Under the group of heavy metals are Cr, Ni, Zn, Cu, Pb and Fe. They are classified under the group of heavy metals because in metallic form they have the densities higher than 4 g/cm 3 . The Cu content in the industrial effluent was found to be minimum of 0.68 ppm in the month of June and maximum of 45.94 ppm in the month of February.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Under the group of heavy metals are Cr, Ni, Zn, Cu, Pb and Fe. They are classified under the group of heavy metals because in metallic form they have the densities higher than 4 g/cm 3 . The Cu content in the industrial effluent was found to be minimum of 0.68 ppm in the month of June and maximum of 45.94 ppm in the month of February.…”
Section: Resultsmentioning
confidence: 99%
“…High levels of pollutants in river/ creek /lake water systems causes an increase in biological oxygen demand (BOD), chemical oxygen demand (COD), total dissolved solids (TDS), total suspended solids (TSS), toxic metals such as Cd, Cr, Ni and Pb and fecal coliform and hence make such water unsuitable for drinking, irrigation and aquatic life [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The Hg concentration in the fish was analyzed to be high in both Thane creek and Ulhas River Estuary, in comparison to the safety limits proposed by WHO (Menon and Mahajan, 2011). A study on the fish consumption pattern revealed that the traditional fishing communities residing in different villages along Ulhas River Estuary and Thane creek are highly dependent on the estuarine/creek fish for their dietary mainstay and consume large quantities of fish (Menon and Mahajan, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…As per the Maharashtra Pollution Control Board (MPCB), the main sources of river water pollution, are the occasional discharge of untreated sewage and industrial effluent in rivers across the state. The pollution data of water bodies due to discharge of industrial waste [6,7,[22][23][24][25][26][27][28][29] points out the need of systematic and regular monitoring of pollution level for further improvement in the industrial waste water treatment methods. We therefore, initiated a study to understand the heavy metals content in the water of Ulhas River along the Dombivli city, situated near Mumbai, India.…”
Section: Introductionmentioning
confidence: 99%